Effectiveness of a Virtual Reality-Based Normal Delivery Preparation Program in Nursing Students: A Follow-Up Study - Boonnate, Nareerat; Kraisit, Minticha; Jaturajanyalert, Netsumol; Tanaisawan, Kritsana (Journal of Thailand Nursing and Midwifery Council, 2025)
Introduction Preparation for normal delivery is a critically important skill for nursing students prior to entering clinical practice. Real-world learning environments often present several limitations, including an insufficient number of patients, unpredictable and uncontrollable clinical scenarios, and potential risks to patient safety. These factors pose significant challenges to the development of clinical competencies and may affect students’ confidence in performing procedures. Virtual reality (VR) technology offers a promising solution by providing realistic, controlled, and safe simulation environments. Through VR, students can repeatedly practice clinical skills without posing any risk to actual patients. Moreover, this hands-on learning approach effectively supports the development of professional competencies in a more efficient and engaging manner. Objectives This study aimed to: 1) examine the outcomes of enhanced preparation for normal delivery beyond the standard criteria on student satisfaction, self-confidence, and clinical skill examination scores in the course “Maternal and Newborn Nursing and Midwifery Practicum 1,” and 2) compare satisfaction with the use of virtual reality technology in simulating normal delivery scenarios, confidence levels, and objective structured clinical examination (OSCE) scores between students who received standard-preparedness and those who received enhanced preparation in the same course. Design This descriptive research employed a prospective data collection approach, applying Garrison’s self-directed learning framework integrated with a comprehensive review of relevant literature to develop strategies for promoting self-directed learning in virtual environments. This conceptual framework enhances learners’ capabilities across multiple dimensions, including self-management, self-monitoring, and motivation for learning. Methodology The participants consisted of 198 second-year nursing students enrolled in the Bachelor of Nursing Science Program at Srisavarindhira Thai Red Cross Institute of Nursing. These students were registered in the course “Maternal and Newborn Nursing and Midwifery I” during the second semester of the 2023 academic year, and in the practicum course of the same title during the first semester of the 2024 academic year. As data were collected from the entire eligible population within the specified timeframe, sample size calculation was not required. Data were collected using the following instruments: a personal information questionnaire; a virtual reality-based normal delivery practice assessment form, which demonstrated a content validity index of 1.00; satisfaction, confidence, and VR-based normal delivery simulation evaluation form, with reliability, Cronbach’s alpha coefficient of .92; and a clinical skill examination form for normal delivery. Descriptive statistics and the Mann–Whitney U test were employed for data analysis, with a significance level set at .05. Results The students in the high-preparedness group, who utilized the VR-based normal labor scenario for self-directed, unlimited practice, achieved higher scores in the Objective Structured Clinical Examination (OSCE) for normal labor clinical skills (M = 26.05, SD = 3.17) compared to those in the Standard-preparedness group (M = 24.73, SD = 3.83), with statistical significance (Z = -2.430, p = .015). However, no statistically significant differences were found between the two groups in terms of satisfaction with the use of VR technology or confidence in performing normal delivery. Recommendation The findings of this study highlight the potential of virtual reality technology in enhancing experiential learning. Therefore, it is recommended that VR-based media be systematically integrated into instructional processes, particularly in courses aimed at developing practical skills. Such integration can help students become familiar with the technology and utilize it as an effective component of advanced learning. As this study employed a comparative research design, future studies should be designed with more rigorous control of relevant variables, particularly through the use of random sampling or clearly defined group allocation.